Policies and guidelines for non-formal education retention in the digital age - Chuleerat Charoenporn; Montouch Maglumtong; Tanpat Kraiwanit (International Journal of Evaluation and Research in Education (IJERE), 2026)
Centering on the Office of Non-Formal and Informal Education (ONIE) Center in Bangkok, this study examines the multifaceted drivers of student dropout within Thailand’s evolving non-formal education system. Employing binary logistic regression on data collected from 428 learners, the analysis integrates demographic, familial, and psychosocial variables to identify statistically significant predictors of disengagement. Key findings reveal that exposure to violence, gender, educational attainment, and sibling-related responsibilities exert substantial influence on dropout likelihood. Specifically, learners tasked with caregiving duties or who had siblings currently enrolled in school exhibited elevated dropout risks. In contrast, those with siblings engaged in employment showed a comparatively lower propensity to disengage from education, suggesting a protective economic and emotional buffer. Notably, over 70% of participants reported prior experiences of violence—a psychosocial factor that emerged as a salient predictor, underscoring the compounded vulnerabilities faced by marginalized learners in urban settings with limited support infrastructure. The final regression model demonstrated strong sensitivity in identifying high-risk individuals and moderate explanatory power (Nagelkerke R²=0.211). These results underscore the imperative for multi-level intervention strategies that address both academic and emotional constraints. By elucidating the intersecting structural and psychosocial dimensions of dropout behavior, this study offers actionable insights to inform targeted retention policies and enhance learner persistence in Thailand’s non-formal education landscape.